2023
DOI: 10.3390/ijms24054651
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Inflammation and Muscle Wasting in Aging and Disease

Abstract: Only in recent years, thanks to a precision medicine-based approach, have treatments tailored to the sex of each patient emerged in clinical trials. In this regard, both striated muscle tissues present significant differences between the two sexes, which may have important consequences for diagnosis and therapy in aging and chronic illness. In fact, preservation of muscle mass in disease conditions correlates with survival; however, sex should be considered when protocols for the maintenance of muscle mass are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 213 publications
3
8
0
Order By: Relevance
“…It may also be related to the bioresistive resistance method we used to detect muscle mass [16] . Moreover, the prevalence was higher in females than in males, which is consistent with the gender differences in the prevalence of sarcopenia under the international diagnostic criteria [14] , and is mainly related to gender differences in hormone levels [17], body composition [18] , muscle ber phenotypes, and neurological differences [19] . In addition, our study found that female patients had a higher BF% and lower muscle lipids than males.Lee and his team has found that skeletal muscle and adipose tissue secrete myokines and adipokines, respectively [20] .…”
Section: Discussionsupporting
confidence: 70%
“…It may also be related to the bioresistive resistance method we used to detect muscle mass [16] . Moreover, the prevalence was higher in females than in males, which is consistent with the gender differences in the prevalence of sarcopenia under the international diagnostic criteria [14] , and is mainly related to gender differences in hormone levels [17], body composition [18] , muscle ber phenotypes, and neurological differences [19] . In addition, our study found that female patients had a higher BF% and lower muscle lipids than males.Lee and his team has found that skeletal muscle and adipose tissue secrete myokines and adipokines, respectively [20] .…”
Section: Discussionsupporting
confidence: 70%
“…The exclusion criteria were strict, and individuals with confirmed cognitive impairment were not participated in the evaluations. Additionally, considering that inflammation in aging is different between men and women 44 , our sample consisted only of older women from the community, which may limit generalizability to other populations. Another limitation of the present study is the fact that it did not explore the participants' diet, as it has been proven that a high-fat diet can interfere with blood leptin concentrations 37 , compared to a standard diet.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that gender differences in muscle atrophy play a role. Studies have shown that aging affects muscle function more in women than in men, and that skeletal muscle attachment quality is lower in older women compared to men [ 15 ]. It is generally accepted that the paraspinal muscles are the dynamic stabilizers of the spine column [ 16 ].…”
Section: Discussionmentioning
confidence: 99%